2D-2D growth of NiFe LDH nanoflakes on montmorillonite for cationic and anionic dye adsorption performance - Jiang, De Bin; Jing, Chuan; Yuan, Yunsong; Feng, Li; Liu, Xiaoying; Dong, Fan; Dong, Biqing; Zhang, Yu Xin (Journal of colloid and interface science, 2019)
[Display omitted] NiFe layered double hydroxides nanoflakes decorated montmorillonite (MMT@NiFe LDH) was successfully prepared by a one-pot hydrothermal method. The 2D-2D growth MMT@NiFe LDH was utilized as an effective adsorbent for removal of anionic dye of methyl orange (MO) and cationic dye of methylene blue (MB). The mole ratio of Ni2+/Fe3+ could quite influence the interlayer spacing, surface area per unit charge and the ultrathin hexagonal laminated morphology of NiFe LDH decorated on the surface of MMT. Various characterization techniques were conducted to identify it, such as XRD, FT-IR, TG-DTA, BET, XPS and SEM. Under the optimal conditions, the Langmuir-fitted maximum adsorption capacities for MO and MB are 108.80 mg g−1 and 99.18 mg g−1, respectively. Adsorption kinetics for MO and MB are both verified to be fit in with pseudo-second-order model. This work suggests a facile pathway to synthesize desirable bifunctional adsorbent for cationic and anionic dyes, which provides the potential application for the actual wastewater purification.